Generation of Organozinc Reagents by Nickel Diazadiene Complex Catalyzed Zinc Insertion into Aryl Sulfonates - Klein, Philippe (Chemistry, 2019)
The generation of arylzinc reagents (ArZnX) by direct insertion of zinc into the C−X bond of ArX electrophiles has typically been restricted to iodides and bromides. The insertions of zinc dust into the C−O bonds of various aryl sulfonates (tosylates, mesylates, triflates, sulfamates), or into the C−X bonds of other moderate electrophiles (X=Cl, SMe) are catalyzed by a simple NiCl(2)–1,4‐diazadiene catalyst system, in which 1,4‐diazadiene (DAD) stands for diacetyl diimines, phenanthroline, bipyridine and related ligands. Catalytic zincation in DMF or NMP solution at room temperature now provides arylzinc sulfonates, which undergo typical catalytic cross‐coupling or electrophilic substitution reactions.